Government spending on research and development and its impact on the human development guide in Singapore for the period 1996-2018 (Entrepreneurship Journal for Finance and Business, 2021)
The research aims to identify the size of government spending on research and development and its impact on the human development index in Singapore, and to analyze and measure the most important indicators of government spending on research and development and the index number for the human development index, and by using some statistical and standard tools, the research has proven that there is a positive effect between spending on research and development. As a percentage of the gross domestic product in Singapore and the human development index in the short term, while in the long term the research proved that there is no relationship between the study variables, while there is a long-term equilibrium relationship at the levels of significance (1%, 5%, 10%), and the results of the tests showed Diagnostic The absence of the self-correlation problem according to the ARCH test, and the study recommended drawing lessons from the Singaporean experience in the field of research and development, creativity, innovation and great progress in the field of education.